THE PROBLEM OF LOGICAL FORM: WITTGENSTEIN AND LEIBNIZ - Piekarski, Michał (Studia Philosophiae Christianae, 2020)
The article is an attempt at explaining the category of logical form used by Ludwig Wittgenstein in his Tractatus logico-philosophicus by using concepts from Gottfried Wilhelm Leibniz’s The Monadology. There are many similarities and analogies between those works, and the key concept for them is the category of the inner and acknowledged importance of consideration based on basic categories of thinking about the world. The Leibnizian prospect allows for a broader look at Wittgenstein’s analysis of the relation between propositions and facts, between language and the world. Using the Hanoverian philosopher’s terminology allows for the demonstration of the ambivalence of the concept of logical form in the philosophy of Wittgenstein and also the metaphysical nature of his first book.